A Review on the Properties of Azadirachta indica, Ocimum tenuiflorum and Cymbopogon citratus (International Journal of Scientific Research and Management (IJSRM), 2021)
Herbal and Medicinal plants are terminologies used for plants around the world as they possess significant therapeutic potential. The objective of this study was to assess the properties and biological activities of these plants as well as their phytochemistry. The results of this study were done descriptively and placed into various tables. Analysis showed that Azadirachta indica possessed eighteen (18) therapeutic properties and sixty-five (65) biologically active compounds, Ocimum tenuiflorum possessed twelve (12) therapeutic properties and eighty-two (82) biologically active compounds were noted and Cymbopogon citratus possessed six (6) therapeutic properties and sixty-four (64) biologically active compounds were reported and analyzed. This study revealed that medicinal and herbal plants have great significance and are greatly overlooked. They can be used to resolve a variety of issues worldwide such as: avoiding microbial and insect resistance in species and even be useful in this time of pandemic against the SARS-CoV-2 (COVD-19 Virus). More studies should be done by health authorities, food authorities, agriculture authorities and other organizations with these plants and other medicinal and herbal plants to maximize their benefits.